Pengaruh Motif Hias Tradisi Megalitik Pada Motif Songket Minangkabau - Eny Christyawaty (Berkala Arkeologi Sangkhakala, 2009)
AbstractDecorative menhir is one of archeological remains in West Sumatra that consists of various forms and sizes. Some decorative motifs are still exist till now, and used as traditional decorative motif of Minangkabau songket weaving.